When opportunity knocks - van Rensburg, Annari; Kyriakakis, Charles; Pecoraro, Alfonso; Herbst, Philip (SA Heart Journal, 2017)
Constrictive pericarditis remains a common medical problem in developing countries where it frequently complicates tuberculous pericarditis. In addition, it is not infrequently seen in the developed world in the context of previous cardiac surgery, chest irradiation and even idiopathic pericarditis.(1) The diagnosis of pericardial constriction is often elusive and delays between the onset of symptoms and final diagnosis is the norm. Given the potential curability of this cause of heart failure and the fact that various features of chronicity in the disease portend a poor prognosis, recognising the disease early is of paramount importance.(1) The haemodynamics of constriction, particularly in more pronounced cases, produces a set of interesting clinical findings that the vigilant physician can elicit. A useful, and often neglected clinical feature, is that of a diastolic precordial or epigastric impulse, the palpable equivalent of an audible diastolic pericardial knock. This short report illustrates this unique clinical finding and explains the haemodynamics responsible for it. We also briefly review other commonly found clinical findings that assist in making the diagnosis of constrictive pericarditis.